THE PARADIGM OF GEOECOLOGICAL CULTURE AND INTERCOMPATIBILITY IN THE IDEAS OF GEOGRAPHIC AND ECOLOGICAL CULTURE - Aynisa Musurmanova; Nusratilla Alimkulov; Dilnoza Abdullaeva (The Bioscan, 2024)
The article is aimed at elucidating the aspects of generality and coherence within the scientific problem of forming students' geographical, ecological and geo-ecological culture, in which this process is interpreted as the result of a natural and vital necessity. According to the authors, issues of education, consciousness, worldview, which are closely related to pedagogical factors, occupy an important place in the formation of geographical, ecological and geoecological culture. If education itself, consciousness and worldview are part of the conditions of formation of a certain culture, then the fact that these factors have many commonalities and integral aspects in the formation of geographical, ecological and geoecological culture expresses the true essence of the article.